Percutaneous Mitral Valve Interventions (Repair): Current Indications and Future Perspectives - Shah, Mahek; Jorde, Ulrich P. (Frontiers in Cardiovascular Medicine, 2019)
Mitral valve regurgitation (MR) is the commonest valvular abnormality encountered among adult patients with cardiac valvular disease and conveys significant morbidity and mortality. The mitral valve is a complex anatomical structure and etiology for regurgitation is classified as either primary or secondary MR. Identification of the etiology in severe MR is critical in determining the appropriate treatment strategy. Transcatheter mitral valve repair (TMVR) is a minimally invasive technique for treatment of selected patients with symptomatic chronic moderate-severe or severe (3 to 4+) MR. While surgery remains the mainstay for treatment in primary MR, several technological advances within the last decade have made transcatheter mitral valve intervention increasingly feasible and safe in clinical practice. Use of TMVR in patients with severe MR has successfully reduced patient symptoms, disease morbidity, improved quality of life, and facilitated reverse remodeling with potential for a survival advantage among certain patients with secondary MR. Recent randomized controlled trials on MitraClip use in secondary MR have reinvigorated interest in this disease and refocused our attention on optimizing patient selection and timing of intervention to maximize benefit from using such percutaneous devices. In our review, we discuss etiologies and pathophysiology in both acute MR and development of chronic severe MR. We discuss management strategies for MR among patients based on etiology, particularly percutaneous mitral valve interventional therapies. We perform an extensive review comparing and contrasting existing data on safety, efficacy, durability and appropriate patient selection related to MitraClip implantation in both primary and secondary MR. Lastly, we explore percutaneous MV therapies beyond the MitraClip as we await larger scale trials on these devices prior to them making way into day-to-day practice.